Modified Bacon’s procedure as repeated sphincter-preserving operation for benign rectal anastomotic stenosis - Xia Wenhao; Huang Ping; Wu Zuoyou; Zhang Weiwei; Weng Heyu; Chen Qi (结直肠肛门外科)
[Objectives] To evaluate the value of modified Bacon’s procedure as repeated sphincter-preserving operation for benign rectal anastomotic stenosis. [Methods] This was a retrospective analysis of 13 patients receiving modified Bacon’s procedure as repeated sphincter-preserving operation for benign rectal anastomotic stenosis at the Affiliated Sir Run Run Hospital of the Nanjing Medical University. We explored the value of this procedure as repeated sphincter-preserving operation for benign rectal anastomotic stenosis. [Results] All surgeries were uneventful. The duration of surgery ranged from 300 to 535 min with an median duration of 384 (330, 458) min. The intraoperative blood loss ranged from 50 to 1 150 mL with an median amount of 375(75, 450) mL. There were no postoperative complications such as postoperative bleeding, anastomotic leakage, anal stenosis, presacral infection, and necrosis of the external bowel. One patient had rectal mucosal prolapse at five months after surgery, this patient underwent resection of prolapsed mucosa and postoperative pelvic floor exercises for sphincter function and showed good recovery. Patients were followed up for 4 months to 3 years. All patients showed good bowel function recovery at 6 months (Willianms score: seven cases were grade A, four were grade B, and one was grade C). In terms of daily bowel movement, five patients had 1~2 times, six patients had 3~4 times, and one patient had >4 times of bowel movement. The remaining one patient who was followed up for 4 months had grade C bowel function and >4 times of bowel movement per day. [Conclusion] For patients with benign rectal anastomotic stenosis who failed multiple mechanical dilatation, endoscopy, interventional treatments, or other non-abdominal surgeries, modified Bacon’s procedure could be considered sphincter-preserving treatment option.